Who Started, Stopped, and Continued Participating in Outdoor Recreation during the COVID-19 Pandemic in the United States? Results from a National Panel Study - B. Derrick Taff; William L. Rice; Ben Lawhon; Peter Newman (Land, 2021)
The COVID-19 pandemic has been proposed as a catalyst for many U.S. residents to re-engage in outdoor recreation or engage in outdoor recreation for the first time. This manuscript describes the results of a representative U.S. national panel study aimed at better understanding the socio-demographic profile (gender, ethnicity, community type, income, and age) of those participants new to outdoor recreation since the start of the COVID-19 pandemic. In doing so, we address how these new outdoor recreationists differ from (1) those who frequently participated in outdoor recreation prior to the pandemic and continue to participate in outdoor recreation, (2) those who did not frequently participate in outdoor recreation prior to the pandemic and remain un-engaged, and (3) those who frequently participated in outdoor recreation prior to the pandemic but stopped their frequent participation following the onset of the pandemic. Results from this U.S. national study suggest that 35.8% of respondents indicated that they did not participate regularly in outdoor recreation prior to the pandemic or during the pandemic, 30.4% indicated that they did participate regularly in outdoor recreation prior to the pandemic and continued to do so regularly during the pandemic, and 13.5% indicated that they did participate regularly in outdoor recreation prior to the pandemic, but did not continue to do so during the pandemic. More than 20% of the sample indicated that they were new outdoor recreationists. The majority of respondents in all categories, including those that were new to outdoor recreation amidst the pandemic, identified as being white, however these new outdoor recreationists were also the least ethnically diverse. The previously but no longer outdoor recreationist respondents were significantly more ethnically diverse than the other three groups, and they tended to live in more urbanized settings. Discussion of these results includes implications for outdoor recreation managers, and researchers who seek to better understand who the COVID-19 pandemic has influenced with regard to outdoor recreation participation. Implications regarding social justice, access and equity to public places that facilitate outdoor recreation, and health-related policies are discussed.